Pediatric multidrug-resistant tuberculosis clinical trials: challenges and opportunities. (March 2017) - McAnaw, S.E.; Hesseling, A.C.; Seddon, J.A.; Dooley, K.E.; Garcia-Prats, A.J.; Kim, S.; Jenkins, H.E.; Schaaf, H.S.; Sterling, T.R.; Horsburgh, C.R.
Highlights: Current barriers to pediatric multidrug-resistant tuberculosis clinical trials are discussed. Recommendations for a science-based framework to address these barriers are presented. Next steps for investigators and funding agencies for responding to this agenda are outlined. Summary: On June 17, 2016, RESIST-TB, IMPAACT, Vital Strategies, and New Ventures jointly hosted the Pediatric Multidrug Resistant Tuberculosis Clinical Trials Landscape Meeting in Arlington, Virginia, USA. The meeting provided updates on current multidrug-resistant tuberculosis (MDR-TB) trials targeting pediatric populations and adult trials that have included pediatric patients. A series of presentations were given that discussed site capacity needs, community engagement, and additional interventions necessary for clinical trials to improve the treatment of pediatric MDR-TB. This article presents a summary of topics discussed, including the following: current trials ongoing and planned; the global burden of MDR-TB in children; current regimens for MDR-TB treatment in children; pharmacokinetics of second-line anti-tuberculosis medications in children; design, sample size, and statistical considerations for MDR-TB trials in children; selection of study population, design, and treatment arms for a trial of novel pediatric MDR-TB regimens; practical aspects of pediatric MDR-TB treatment trials; and strategies for integrating children into adult tuberculosis trials. These discussions elucidated barriers to pediatric MDR-TB clinical trials and provided insight into necessary next steps for progress in this field. Investigators and funding agencies need to respond to these recommendations so that important studies can be implemented, leading to improved treatment for children with MDR-TB.